Por que comprar uma nova casa? contradições entre as necessidades habitacionais dos mais pobres e a implementação do Programa Minha Casa Minha Vida na cidade de Maceió, Alagoas - Melo , Tainá Silva (2017)
The Minha Casa Minha Vida Program was released in 2009 and opens a series of news arguments about Brazilian urban issues. Its have been pointed limits about as the format of the policy as the architectural and urban characteristics of the produced projects. However, there aren’t completed studies about the impact of the PMCMV on the access of the poorest people to decent dwelling. This thesis advances in these investigations by questioning the role of Social Housing at the scope of a housing policy all focused on housing production and that do not debate the population’s inclusion in the cities’ benefits or to consider the poorest people’s real housing needs."Why buy a new house?" in the scope of the PMCMV, is the work’s question, debated here through differents points of view, as the academic papers as resident’s opinions about the news buildings. The city of Maceió, Alagoas’ capital, at Brazilian Northeast, was chosen as the empirical basis for the discussions. The thesis has a qualitative character and is developed from five points: i) relationship between the production of urban spaces and the housing of the poorest in the cities; ii) housing needs of the poorest; iii) data and academic debate about the PMCMV; (iv) housing financed by the PMCMV; and (v) residents of social housing financed by the PMCMV. Data collection and academic studies indicated that, with the PMCMV, the housing policy is again subjected to the formal real estate market‘s logic (profitability), thus, standardized housing mega-projects are built on places whithout infrastructure (where land is cheaper). As a result, old practices of Brazilian urban spaces production are reproduced. In Maceió, 87% of the population is within the income limit of the PMCMV, but the greatest need of the poorest, who live in precarious settlements in this city, is not the replacement of their homes but the creation of infrastructure.The results of the interviews with the residents pointed out that the PMCMV served mainly families that did not have access to real estate credit and lived in rented houses, at the expense of those who lived in informal, irregular or illegal situations.The declarations of the interviewees show that this program served to facilitate access to real estate credit for those who did not previously meet market requirements, increasing access to home ownership, but the living conditions of the poorest in Maceió were not changed. There were, however, exceptions to this rule, such as the Conjunto Residencial Ouro Preto, built on land with access to urban infrastructure and services, for the accommodation of a community previously located on an area subjected to floods and landslides. They fought 10 years to finally conquer decent dwelling. Such exceptions must become the rule in order to ensure that the people most in need of public support are actually addressed.